2003
DOI: 10.1055/s-2003-39475
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into How Adipocytes Sense their Triglyceride Stores. Is Cholesterol a Signal?

Abstract: In recent years, our view of adipose tissue has evolved from a passive sink for energy storage to an active tissue producing multiple molecules acting on various tissues in different aspects of energy homeostasis. The production of adipose-derived secretory products is tightly regulated as a function of adipocyte lipid accumulation, but the mechanisms by which fat cells are able to sense the levels of their triglyceride stores still remains largely unknown. This paper reviews new insights into this question ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…It has been reported that de novo cholesterol synthesis is limited in adipocytes [3]. Consistently, treatment with inhibitors that suppress cholesterol synthesis (mevastatin or U18666A) [7, 23] did not alter cholesterol levels in differentiated 3T3-L1 adipocytes even up to 24 h incubation (S1 Fig).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…It has been reported that de novo cholesterol synthesis is limited in adipocytes [3]. Consistently, treatment with inhibitors that suppress cholesterol synthesis (mevastatin or U18666A) [7, 23] did not alter cholesterol levels in differentiated 3T3-L1 adipocytes even up to 24 h incubation (S1 Fig).…”
Section: Resultssupporting
confidence: 77%
“…Additionally, we confirmed that MβCD and filipin treatment disturbed the integrity of lipid rafts in adipocytes (Fig 6C). Because cholesterol redistribution was observed in hypertrophied adipocytes [13, 5–7], the depletion of membrane cholesterol in obese adipocytes may result in a disturbance of the lipid raft function, leading to elevated MCP-1 expression and secretion and activation of proinflammatory signaling pathways such as ERK and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steroids were mainly composed of cholesterol. Studies have shown that insufficient cholesterol content could cause more free fatty acid (FFA) to remain in the circulatory system of mice to provide energy sources for other tissues and organs of the animal body (Dugail et al, 2003). In our study, compared with the control group, the squalene epoxidase (SQLE), lanosterol synthase (LSS), 24-dehydrocholesterol reductase (DHCR24), 7-dehydrocholesterol reductase (DHCR7), and lanosterol synthase (LSS) genes encoding proteins related to cholesterol synthesis were significantly down-regulated in the cold acclimation group.…”
Section: Discussionmentioning
confidence: 99%